Implementing Unity Elements in the Islamic Studies Curriculum - Khasasi, Mohd Zuhdi Ahmad; Salleh , Ahmad Dahlan; Yahaya, Mohammad Zaini (International Journal of Psychosocial Rehabilitation, 2020)
In response to the unifying recommendations in the Malaysian Education Development Plan (PPPM) 2013-2025, the Revised 2017 Primary School Curriculum (KSSR) brought a form of transformation in the content-s of Islamic Education textbooks, which included the addition of an explicitly translated unity element through 3 unity constructs namely Accepting, Respecting and Managing Diversity with each construct has its subconstructs. As a result of this transformation, teachers are required to adopt these elements to themes related to unity without changing the discipline and content of existing Islamic Education subjects, thus raising questions about the breadth of content of the textbook in accommodating them. Therefore, this research intends to review the scope and adequacy of the contents of the Revised 2017 Primary School Curriculum of Islamic Education textbook for Standard 3 in accepting the application of these elements. This study is a qualitative research based on content analysis design concerning literature review through document analysis and thematic analysis. The results show that the contents of the Standard 3 are rich in elements of unity. Although the amount of distribution is uneven, it can be developed through various approaches such as Beyond-Curriculum Elements (EMK) and Higher-Order Thinking Skills (KBAT). The implication is that teachers need to be sensitive in interpreting and developing elements of unity through a variety of integrated approaches as an initiative to produce students who are capable of accepting, respecting and managing diversity.